The Activity of residents in Belida River, are affecting water quality conditions, and the presence of organisms in it. One of the biota that has an important role in these waters is periphyton. The study aims to determine the abundance and diversity of p - Marini, Melfa (Widyariset, 2013)
The Activity of residents in Belida River, are affecting water quality conditions, and the presence of organisms in it. One of the biota that has an important role in these waters is periphyton. The study aims to determine the abundance and diversity of periphyton in Belida river waters around District Muara Enim. A descriptive exploratory study was conducted from February to November 2011. The results recorded 36 genera of periphyton belong to three classes namely Bacillariophyceae, Chlorophyceae and Cyanophyceae. Diversity index (H â) ranged from 0.74 to 2.15. It is concluded that the diversity of periphyton in the waters of the River Belidawas low, with Ulotrik species, Nitzschia, and Synedra being the Dominant.